The Tentmaking Ministry of Apostle Paul and its Replication in the Redeemed Christian Church Of God, Nigeria - FELIX AKINTUNDE (African Theological Journal for Church and Society)
Insufficient remuneration is given to gospel ministers in many Nigerian churches. Some churches may not even pay their ministers regularly. Undoubtedly, many churches have fallen short of their financial support commitments to their clergy. However, Apostle Paul renounced his claim to receive financial assistance from the church and chose to work with his hands to protect the gospel’s integrity lest the gospel be hindered. This paper, therefore, addresses the tentmaking ministry of Apostle Paul and its replication in the Redeemed Christian Church of God (RCCG), Nigeria. The paper adopted the historical-critical exegetical method to explain the chosen biblical texts and the ethnographic method to elicit data from respondents in the RCCG, Oyo Province 9, Oyo State, Nigeria. The study reveals that many RCCG pastors adopted the tentmaking method of Apostle Paul, labouring diligently to expand the church of Christ without taking remuneration from the church after the order of Apostle Paul.